Effect of Electrolysis Technology on Saline Water under Utilize Nano-coated Electrodes - Mohamed Hassan; Arafa Yasser; Khaled elbagoury (Arab Universities Journal of Agricultural Sciences, 2021)
In this work, electromagnetic field technol-ogy and electrolysis technology with alumi-num electrodes coated with titanate nano-coat-ing were combined in different investigated parameters: power types (Electrolysis pass (EP) and Electromagnetic pass (EMP)), volt-age (12v, 24v and 36v) and nano-coating pa-rameters (coated and uncoated). The designed water treatment unit was evaluated by record-ing the EC-meter readings for 60min (each 5min) at a flow rate of 5l/min. Results show that the best salt rejection rate was 3.4% when EMP was used before EP where four elec-trodes were coated. In contrast, the other pa-rameters (EP, EMP+EP and EMP+EP (2 coated electrodes and 2 uncoated)) recorded the salt rejection rates 1.13%, 1.57% and 2.4%, respectively. This study is promising and opens the way for integrating both electrolysis and electromagnetic field technologies with on-farm irrigation systems and enhancing their efficiency using nanotechnology.